Preservation of parathyroid glands during thyroid and neck surgery - Rao, Smitha S.; Rao, Himagirish; Moinuddin, Zia; Rozario, Anthony P.; Augustine, Titus (Frontiers in Endocrinology, 2023)
The parathyroid glands are situated in close proximity to the thyroid gland. They have an important endocrine function maintaining calcium and phosphate homeostasis in the body by the secretion of parathormone (PTH), which is responsible for this function. The parathyroid glands are commonly damaged during thyroid surgeries. This could lead to transient or permanent hypoparathyroidism in 30% of cases. Preservation of the parathyroid glands, is an important and integral part of thyroidectomy and other surgical interventions in the neck. The main principle underlying this is a thorough understanding of parathyroid anatomy in relation to the thyroid gland and other important structures in the area. There can also be significant variation in the anatomical location of the glands. Various techniques and methods have been described for parathyroid preservation. They include intraoperative identification utilising indocyanine green (ICG) fluorescence, carbon nanoparticles, loupes, and microscopes. The techniques of surgery (meticulous capsular dissection), expertise, central compartment neck dissection, preoperative vitamin D deficiency, extent and type of thyroidectomy are the risk factors associated with damaged thyroids, inadvertent parathyroidectomy and subsequent hypoparathyroidism. Parathyroid Autotransplantation is a treatment option for inadvertent parathyroidectomy. Ultimately, the best way to assure normal parathyroid function is to preserve them in situ intraoperatively undamaged.